Beyond the vessel: Fostering adoption of innovation and change in adult education practice - Michael K. Turner; John M. Dirkx (Adult Education Research Conference, 1994)
Recent studies suggest that continuing professional education (CPE) programs utilizing traditional "update" models are relatively ineffective in facilitating actual change in practice. This study investigated the efficacy of a "commitment to change" (CTC) strategy as a means of fostering intended change in the practice of adult educators.